Nocturnal Atrial Fibrillation Caused by Mutation in KCND2, Encoding Pore-Forming (α) Subunit of the Cardiac Kv4.2 Potassium Channel. (November 2018) - Drabkin, Max; Zilberberg, Noam; Menahem, Sasson; Mulla, Wesam; Halperin, Daniel; Yogev, Yuval; Wormser, Ohad; Perez, Yonatan; Kadir, Rotem; Etzion, Yoram; Katz, Amos; Birk, Ohad S.
Abstract : Background: Paroxysmal atrial fibrillation (AF) can be caused by gain-of-function mutations in genes, encoding the cardiac potassium channel subunits KCNJ2, KCNE1, and KCNH2 that mediate the repolarizing potassium currents Ik1, Iks, and Ikr, respectively. Methods: Linkage analysis, whole-exome sequencing, and Xenopus oocyte electrophysiology studies were used in this study. Results: Through genetic studies, we showed that autosomal dominant early-onset nocturnal paroxysmal AF is caused by p.S447R mutation in KCND2, encoding the pore-forming (α) subunit of the Kv4.2 cardiac potassium channel. Kv4.2, along with Kv4.3, contributes to the cardiac fast transient outward K + current, Ito . Ito underlies the early phase of repolarization in the cardiac action potential, thereby setting the initial potential of the plateau phase and governing its duration and amplitude. In Xenopus oocytes, the mutation increased the channel's inactivation time constant and affected its regulation: p.S447 resides in a protein kinase C (PKC) phosphorylation site, which normally allows attenuation of Kv4.2 membrane expression. The mutant Kv4.2 exhibited impaired response to PKC; hence, Kv4.2 membrane expression was augmented, enhancing potassium currents. Coexpression of mutant and wild-type channels (recapitulating heterozygosity in affected individuals) showed results similar to the mutant channel alone. Finally, in a hybrid channel composed of Kv4.3 and Kv4.2, simulating the mature endogenous heterotetrameric channel underlying Ito, the p.S447R Kv4.2 mutation exerted a gain-of-function effect on Kv4.3. Conclusions: The mutation alters Kv4.2's kinetic properties, impairs its inhibitory regulation, and exerts gain-of-function effect on both Kv4.2 homotetramers and Kv4.2-Kv4.3 heterotetramers. These effects presumably increase the repolarizing potassium current Ito, thereby abbreviating action potential duration, creating arrhythmogenic substrate for nocturnal AF. Interestingly, Kv4.2 expression was previously shown to demonstrate circadian variation, with peak expression at daytime in murine hearts (human nighttime), with possible relevance to the nocturnal onset of paroxysmal AF symptoms in our patients. The atrial-specific phenotype suggests that targeting Kv4.2 might be effective in the treatment of nocturnal paroxysmal AF, avoiding adverse ventricular effects. Abstract : Supplemental Digital Content is available in the text.